1996
DOI: 10.1128/mcb.16.9.4897
|View full text |Cite
|
Sign up to set email alerts
|

The EH-Domain-Containing Protein Pan1 Is Required for Normal Organization of the Actin Cytoskeleton in Saccharomyces cerevisiae

Abstract: Normal cell growth and division in the yeast Saccharomyces cerevisiae involve dramatic and frequent changes in the organization of the actin cytoskeleton. Previous studies have suggested that the reorganization of the actin cytoskeleton in accordance with cell cycle progression is controlled, directly or indirectly, by the cyclindependent kinase Cdc28. Here we report that by isolating rapid-death mutants in the background of the Start-deficient cdc28-4 mutation, the essential yeast gene PAN1, previously though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(145 citation statements)
references
References 61 publications
10
135
0
Order By: Relevance
“…We could not, however, detect an interaction between Scd5p and Sla1p, another endocytic protein that associates with Pan1p and End3p in vivo (Tang et al, 2000), by the two-hybrid assay (data not shown). In support of the finding that Scd5p interacts with both Pan1p and End3p, a temperature-sensitive mutant of scd5 defective in endocytosis and actin organization, scd5-1 Huang et al, 2003), exhibited synthetic lethality with either pan1-4 (Tang and Cai, 1996), or end3⌬ ( Figure 1E), indicating that these genes have functions in common. Together, these experiments confirm a physical and functional association between Scd5p and the Pan1p-End3p complex, thus making Scd5p a possible link between Glc7p and Pan1p for the dephosphorylation purpose.…”
Section: Interaction Of Scd5p With Pan1p and End3psupporting
confidence: 57%
See 1 more Smart Citation
“…We could not, however, detect an interaction between Scd5p and Sla1p, another endocytic protein that associates with Pan1p and End3p in vivo (Tang et al, 2000), by the two-hybrid assay (data not shown). In support of the finding that Scd5p interacts with both Pan1p and End3p, a temperature-sensitive mutant of scd5 defective in endocytosis and actin organization, scd5-1 Huang et al, 2003), exhibited synthetic lethality with either pan1-4 (Tang and Cai, 1996), or end3⌬ ( Figure 1E), indicating that these genes have functions in common. Together, these experiments confirm a physical and functional association between Scd5p and the Pan1p-End3p complex, thus making Scd5p a possible link between Glc7p and Pan1p for the dephosphorylation purpose.…”
Section: Interaction Of Scd5p With Pan1p and End3psupporting
confidence: 57%
“…As shown in Figure 4A, the glc7-td mutant exhibited a grossly distorted actin cytoskeleton after a prolonged incubation at 37°C (6 h) to diminish the Glc7p protein content ( Figure 4A, center). The majority of glc7-td cells contained large and aberrant actin aggregates similar to those found in the pan1-4, scd5-1, and end3⌬ mutants (Benedetti et al, 1994;Tang and Cai, 1996;Huang et al, 2003). In contrast, the control cells (glc7-ntd) maintained a normal pattern of actin cytoskeleton after the same treatment ( Figure 4A, top), suggesting that the actin abnormalities in glc7-td cells were caused by the phosphatase depletion.…”
Section: Partial Suppression Of Glc7-td By Prk1⌬mentioning
confidence: 82%
“…In view of these results, we conclude that Arp2p is involved in the internalization step of endocytosis, as are a growing number of components of the actin cytoskeleton (Kubler and Riezman, 1993;Benedetti et al, 1994;Munn et al, 1995;Tang and Cai, 1996;Wendland et al, 1996). The synthetically lethal interaction we found between end3-1 and arp2-1 mutations suggests interaction between Arp2p and End3p, although the mechanism of interaction is unknown.…”
Section: Fm 4-64 Stainingmentioning
confidence: 69%
“…Similarly, type I myosins (Myo3p and Myo5p) were shown to be required for actin cytoskeleton organization and for fluid-phase and receptor-mediated endocytosis (Geli and Riezman, 1996;Goodson et al, 1996). Finally, a recent screen for endocytic mutants based on sorting cells defective for internalization of the lipophilic dye [N-(3-triethylammoniumpro-pyl)-4-(p-diethylaminophenylhexatrienyl)pyridinium dibromidel led to the identification of DIM1 and DIM2 genes (Wendland et al, 1996), respectively allelic to SHE4 (Jansen et al, 1996) and PAN1 Deardoff, 1992, 1995;Tang and Cai, 1996), both of which are also required for normal distribution of the actin cytoskeleton. Thus, a number of mutant proteins that alter cortical actin distribution cause a block in the internalization step of endocytosis and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Both EH domains consist of EF hand that is a common helix ± loop ± helix structural motif that binds calcium via conserved negatively charged side chains in the loop (Heizmann and Hunziker, 1991), and indeed they bind to calcium (de Beer et al, 1998;Koshiba et al, 1999). Screening with a multivalent nonapeptide phage display library has revealed that ten of thirteen EH domains from (Tang and Cai, 1996;Di Fiore et al, 1997;Haner et al, 1997;Tang et al, 1997;Wendland and Emr, 1998). Similar to many cell surface receptors, the insulin receptor is internalized into intracellular vesicular compartments following ligand binding and tyrosine kinase activation (Levy and Olefsky, 1987;Backer et al, 1989).…”
Section: Discussionmentioning
confidence: 99%